(untitled) (Pedagogical Cluster-Journal of Pedagogical Developments, 2023)
In the current competitive context, innovation has become a necessity, to the point that it seems that no company can survive without developing innovation processes. One of the great concerns of small and medium-sized companies is about the investment of resources in innovation activities and their success. Therefore, this article analyzes the influence of different innovation activities performed by small and medium-sized enterprises (SMEs) of the Colombian Caribbean region on their product innovation outcomes and thereby provides a solid groundwork for the design of innovation strategies. To achieve this objective, a data collection instrument was first validated in 56 SMEs, followed by the application of a reflective measurement model with convergent validity analysis. The results of the model application revealed that investment in Research and Development (R&D) and innovation, knowledge transfer, technology adoption, and financial aspects explain to a greater extent the introduction of new products to the market.